Sex education research a look between the sheets - Taverner, William J. (Routledge, 2023)
Curated by the chief editor of the American Journal of Sexuality Education, this book presents engaging and accessible chapters that capture current and essential research findings from leaders in the sexuality education field. William J. Taverner brings together an impressive array of contributors to help sexuality professionals remain up-to-date on the most relevant issues in sex education today. Covering a spectrum of hot sexuality education topics, including abstinence, gender, innovative programs, pleasure, the politics of sexuality education, porn literacy, sexual orientation, and more, each chapter describes key findings on a particular topic, their significance, their practical application, and how these new developments have arrived. The book includes chapters that address individuals across all age ranges, from children to older adults, as well as sexuality education and training programs for specialized professions, such as nurses and school-based health occupations. Practical and clear, this book identifies priorities and trends in the field, addresses marginalized audiences and overlooked topics, and hopes to encourage important discussions to come. Sex Education Research: A Look Between the Sheets provides a wide range of occupations and academic disciplines with a foundation of research essential to their work, such as public health professionals and students of human sexuality, gender studies, biology, psychology, sociology, as well as community educators, school nurses and health teachers, and administrative leaders affiliated with sexuality education programs at community-based organizations.